Extended Frequency-Directed Run-Length Code with Improved Application to System-on-a-Chip Test Data Compression - El-Maleh, Aiman H. (2002)
One of the major challenges in testing a System-on-a-Chip (SOC) is dealing with the large test data size. To reduce the volume of test data, several test data compression techniques have been proposed. Frequency-directed run-length (FDR) code is a variable-to-variable run length code based on encoding runs of 0’s. In this work, we demonstrate that higher test data compression can be achieved based on encoding both runs of 0’s and 1’s. We propose an extension to the FDR code and demonstrate by experimental results its effectiveness in achieving higher compression ratio.